2013
DOI: 10.1016/j.ijintrel.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and social attitudes among majority children

Abstract: Article (Unspecified) http://sro.sussex.ac.uk Aronson, Krista Maywalt and Brown, Rupert (2013) Acculturation and social attitudes among majority children. International Journal of Intercultural Relations, 37 (3). pp. 313-322. ISSN 0147-1767 This version is available from Sussex Research Online: http://sro.sussex.ac.uk/52956/ This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
(56 reference statements)
1
9
0
1
Order By: Relevance
“…However, the current findings are equivocal regarding whether one extended contact message is more effective than another: dual identity was associated with the highest behavioral intention scores in the United States; but, dual identity and common group messages were associated with equally positive outcomes within the Italian sample. These results somewhat mirror the extended contact research landscape in which some research links dual identity messages with the most positive outcomes (Cameron et al, ), and the endorsement of acculturative attitudes that emphasize both contact with mainstream culture and cultural maintenance (integration) with prosocial intergroup attitudes and behavioral intentions among majority children (Aronson & Brown, ), whereas other findings do not distinguish between common group or dual identity messages (Cameron, Rutland, Turner, et al, ). For instance, Cameron Rutland, Turner, et al () speculate that common group messages may be equally effective in environments where the minority group category is already salient for children, predisposing them to consider both superordinate and subordinate categories during story reading.…”
Section: Discussionsupporting
confidence: 77%
“…However, the current findings are equivocal regarding whether one extended contact message is more effective than another: dual identity was associated with the highest behavioral intention scores in the United States; but, dual identity and common group messages were associated with equally positive outcomes within the Italian sample. These results somewhat mirror the extended contact research landscape in which some research links dual identity messages with the most positive outcomes (Cameron et al, ), and the endorsement of acculturative attitudes that emphasize both contact with mainstream culture and cultural maintenance (integration) with prosocial intergroup attitudes and behavioral intentions among majority children (Aronson & Brown, ), whereas other findings do not distinguish between common group or dual identity messages (Cameron, Rutland, Turner, et al, ). For instance, Cameron Rutland, Turner, et al () speculate that common group messages may be equally effective in environments where the minority group category is already salient for children, predisposing them to consider both superordinate and subordinate categories during story reading.…”
Section: Discussionsupporting
confidence: 77%
“…Hierarchical and K Means cluster analyses were conducted to explore the acculturation profiles of youngsters of migrant background living in Catalonia. Cluster analysis was chosen, rather than median split, because it identifies emergent patterns in the data instead of imposing an a priori structure (Aronson and Brown 2013). The cluster analysis was based on participants' answers to nine variables regarding the maintenance of their culture of origin and the adoption of the Catalan and the Spanish cultures in the context of education.…”
Section: Instrumentsmentioning
confidence: 99%
“…According to previous studies (e.g. Aronson and Brown 2013;Brown, Gibbons, and Hughes 2013), the first step of the analysis consisted of a hierarchical cluster analysis using Ward's method on squared Euclidean distances to determine the number of clusters that best fitted the data. The optimal number of clusters was found to be four.…”
Section: Instrumentsmentioning
confidence: 99%
“…Acculturation refers to processes of cultural adjustments that occur due to prolonged contact between groups of people that are culturally different (Berry 1997). It was previously viewed as a one-way process where migrants abandoned their cultural beliefs and values and adopted those of their host country (Aronson and Brown 2013;Schwartz, Unger, Zamboanga and Szapocznik 2010). Research has shown, however, that acquiring the beliefs, values, and practices of the host country does not automatically imply that migrants discard those of their country of origin (Schwartz et al 2010), and a number of conceptual models of acculturation have been adopted in order to explain the changes that take place when different groups of people and individuals are interacting (Berry 1980;Kramer 2012).…”
Section: Pre-and Post-migration Experiencesmentioning
confidence: 99%